Environmentally relevant concentrations of benzophenones triggered DNA damage and apoptosis in male Chinese rare minnows (Gobiocypris rarus). (June 2022) - Yan, Saihong; Wang, Jun; Zheng, Ziting; Ji, Fenfen; Yan, Liang; Yang, Lihua; Zha, Jinmiao
Graphical abstract: Highlights: Cell cycle, DNA replication and repair were significantly altered pathways. 50 and 500 μg/L BPs significantly increased DNA damage and 8-OHdG levels. Hepatic apoptotic rates were significantly increased after 500 μg/L BPs treatments. The activities of caspase-3, -8 and -9 were significantly increased. BP, BP-1 and BP-4 bind to caspase-3 with different binding interactions. Abstract: Benzophenone-type ultraviolet (UV) filters (BPs) are commonly used as sunscreen agents, fragrance enhancers and plastic additives, and are great threats to aquatic organisms due to their high detected concentrations in the aquatic environment. However, few studies on their toxicity and mechanism in fish have been clearly reported. In this study, Chinese rare minnows ( Gobiocypris rarus ) were exposed to benzophenone (BP), 2, 4-dihydroxybenzophenone (BP-1), and 5-benzoyl-4-hydroxy-2-methoxybenzenesulfonic acid (BP-4) at 5, 50, 500 µg/L for 28 d to assess their toxicity. Transcriptomics screening showed that cell cycle, DNA replication and repair were significantly altered pathways ( p  < 0.05). The altered transcripts were similar to those identified by RNA-seq. DNA damage and 8-OHdG levels were significantly increased at 50 and 500 μg/L groups ( p  < 0.05). The DNA methylcytosine level was not significantly changed exposure to BP, BP-1 and BP-4. TUNEL assays indicated that hepatic apoptosis was significantly improved at 500 μg/L BP and BP-4 and 50 and 500 μg/L BP-1 ( p  < 0.05), with the significantly increasing the activity of caspase-3, -8 and -9 ( p  < 0.05). Molecular docking analysis revealed that BP, BP-1 and BP-4 could bind differently to caspase-3 through different binding interactions. Therefore, BP-1 induced more serious oxidative DNA damage and apoptosis by activating caspase-3 than BP and BP-4, which will provide theoretical basis and data support for ecological evaluation of aquatic organisms induced by BPs.